(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In order to survive in the cut throat competition, the banking sector has been adopting technical aspects. The information communication technological aspects of the banks help to attain the competitive advantage over the other. This research paper is emphasized to evaluate the information and communication technologies adopted by the banking sector in India. However, this paper is also aimed to assess the impact of information and communication technology in the Indian banking. The study focused to understand this scenario in the Indian rural sector. The samples are drawn from 300 rural banking customers and analyzed the data.